2019
DOI: 10.1073/pnas.1903432116
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA EMS connects c-Myc to cell cycle control and tumorigenesis

Abstract: Deregulated expression of c-Myc is an important molecular hallmark of cancer. The oncogenic function of c-Myc has been largely attributed to its intrinsic nature as a master transcription factor. Here, we report the long noncoding RNA (lncRNA) E2F1 messenger RNA (mRNA) stabilizing factor (EMS) as a direct c-Myc transcriptional target. EMS functions as an oncogenic molecule by promoting G1/S cell cycle progression. Mechanistically, EMS cooperates with the RNA binding protein RALY to stabilize E2F1 mRNA, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 73 publications
4
59
0
Order By: Relevance
“…expression peaked in G1 phase, and its knockdown gave growth inhibition in all four cell lines, enrichment of cells in the G1 phase by 3-7 percentage points and a corresponding reduction of cells present in the S phase. These results are in line with a previous functional study of RP11−132A1.4 in A549 cells[47]. In addition to reporting similar growth inhibition and enrichment of cells in G1 phase, the study revealed that RP11−132A1.4, there named E2F1 mRNA stabilizing (EMS) lncRNA, is a direct transcriptional target of c-MYC.…”
supporting
confidence: 91%
“…expression peaked in G1 phase, and its knockdown gave growth inhibition in all four cell lines, enrichment of cells in the G1 phase by 3-7 percentage points and a corresponding reduction of cells present in the S phase. These results are in line with a previous functional study of RP11−132A1.4 in A549 cells[47]. In addition to reporting similar growth inhibition and enrichment of cells in G1 phase, the study revealed that RP11−132A1.4, there named E2F1 mRNA stabilizing (EMS) lncRNA, is a direct transcriptional target of c-MYC.…”
supporting
confidence: 91%
“…3A, B), we hypothesized that TANAR could modulate TWIST1 mRNA stability via the TANAR-TWIST1 interaction, as was shown with the presence of TANAR in TWIST1 pull-down assay (See Fig. 3E) (43,45,46). Indeed, mRNA stability assay, using treatment with Actinomycin, revealed that knocking down TANAR could block the overexpressing AR-increased TWIST1 mRNA stability (Fig.…”
Section: Mechanism Dissection Of How Tanar Can Alter Twist1 Expressiomentioning
confidence: 65%
“…As with the protein-coding transcripts, the transcription of lncRNAs is also controlled by the transcriptional factors. 28 , 29 As an example, lncRNA HAS2 - AS1 was upregulated by transcription factor cAMP responsive element-binding protein1 in epithelial ovarian cancer, and then promoted the tumorigenesis of epithelial ovarian cancer by regulating miR-466 / RUNX family transcription factor 2 axis. 30 Recently, STAT3 has been reported to play an important role in various malignancies.…”
Section: Discussionmentioning
confidence: 99%